Fast ion conductor modified positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric device

CN119297271APending Publication Date: 2025-01-10TIANJIN B&M SCI & TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350788.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

然而镍含量中等的锂镍锰钴氧化物的一次颗粒较大,电子导电性和离子导电性较差,限制其容量释放

Benefits of technology

[0036] The fast ion conductor modified cathode material provided above contains a fast ion conductor in the coating layer. During the co-baking process of the coating raw material and the core, some cations of the fast ion conductor will penetrate into the core. Due to the fast ion conductor Doped with R element, the R element enters the lithium sites of the lithium nickel manganese cobalt oxide in the core to expand the interlayer spacing of the layered structure and improve the Li + Migration rate; the fast ion conductor coating layer has a stable lithium ion diffusion channel, and a complete coating is constructed on the surface of lithium nickel manganese cobalt oxide. Since the fast ion conductor containing Ti element itself has good electronic conductivity, this The coating layer improves the electron conductivity of the cathode material. At the same time, the coating layer allows other ions, including lithium ions, to migrate therein. Therefore, the coating layer also improves the ionic conductivity of the cathode material. In addition, the coating layer has a better effect of isolating the electrolyte and inhibiting side reactions between the electrolyte and the core surface. Part of the Ti element diffuses into the interior of the lithium nickel manganese cobalt oxide to form Ti-O bonds. Since the Ti-O bonds have relatively strong The high bond energy can better inhibit the precipitation of oxygen on the core surface. In summary, coating the core with a coating layer containing fast ion conductors can improve the electronic conductivity and ion conductivity of the cathode material, reduce the charge transfer resistance, increase the capacity of the cathode material, and extend the life of the battery using the cathode material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297271A_ABST
    Figure CN119297271A_ABST
Patent Text Reader

Abstract

The invention provides a fast ion conductor modified positive electrode material, a preparation method of the fast ion conductor modified positive electrode material, a positive electrode plate, a lithium ion battery and an electric device. The fast ion conductor modified positive electrode material comprises an inner core and a coating layer coating at least part of the surface of the inner core, the inner core comprises a lithium nickel manganese cobalt oxide, the coating layer comprises a fast ion conductor, the chemical formula of the fast ion conductor is Li2-xRxTi3QO8, x is greater than 0 and less than or equal to 1, the R element comprises one or more of Na and K, and the Q element comprises one or more of Co, Mg, Ni and Mn. By adopting the titanium-containing fast ion conductor for coating, the ion conductivity and the electronic conductivity of the core material can be improved, the impedance is reduced, the capacity is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a fast ion conductor modified positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and an electrical device. Background Art

[0002] Lithium-ion batteries are widely used in portable devices, electric vehicles, grid energy storage and other areas of life due to their high energy density, good rate performance and zero memory effect. As a key component of lithium-ion batteries, cathode materials determine their overall cost and energy density. The development of high-performance cathode materials is of great significance for the construction of a new generation of lithium-ion battery packs.

[0003] In recent years, lithium nickel manganese cobalt oxide (e.g. LiNi x Co y Mn 1−x−y O2, x ≥ 0.6) has become the most promising lithium battery positive electrode material due to its advantages such as high specific capacity and low cost. However, the primary particles of lithium nickel manganese cobalt oxide with medium nickel content are large, and its electronic conductivity and ionic conductivity are poor, which limits its capacity release. Summary of the invention

[0004] Based on this, the present application provides a fast ion conductor modified positive electrode material and its preparation method, positive electrode plate, lithium ion battery and power-consuming device to improve the electronic conductivity and ionic conductivity of the positive electrode material and increase the capacity of the positive electrode material.

[0005] The first aspect of the present application provides a fast ion conductor modified positive electrode material, comprising:

[0006] a core comprising lithium nickel manganese cobalt oxide; and

[0007] A coating layer is coated on at least a portion of the surface of the core, wherein the coating layer comprises a fast ion conductor, wherein the chemical formula of the fast ion conductor is Li 2-x R x Ti3QO8, 0<x≤1, R element includes one or more elements of Na and K, and Q element includes one or more elements of Co, Mg, Ni and Mn.

[0008] In some embodiments, the sum of the mass proportions of the R element and Ti contained in the fast ion conductor in the positive electrode material is 0.1%-1%.

[0009] In some embodiments, the mass ratio of Ti contained in the fast ion conductor in the positive electrode material is 1000 ppm-3000 ppm.

[0010] In some embodiments, the fast ion conductor is coated on at least a part of the surface of the lithium nickel manganese cobalt oxide.

[0011] In some embodiments, the chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements among Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B.

[0012] In some embodiments, the core includes one or more of single crystal particles, pseudo single crystal particles, and polycrystalline particles.

[0013] In some embodiments, the volume average particle size Dv501 of the single crystal particles is 2.5 μm - 4.5 μm.

[0014] In some embodiments, the volume average particle size Dv502 of the polycrystalline particles is 1.5 μm - 18 μm.

[0015] The second aspect of the present application provides a method for preparing a fast ion conductor modified cathode material, including the following steps:

[0016] Performing a first calcination treatment on a mixture containing a core, a lithium salt, a Ti source, an R source, and a Q source to prepare the cathode material; or

[0017] Immersing the core into a mixed solution containing a lithium salt, a Ti source, an R source, and a Q source, filtering and separating after immersing for a preset time, and performing a first calcination treatment on the solid obtained by filtering and separating to prepare the cathode material; or

[0018] Mixing the core with a mixed solution containing a lithium salt, a Ti source, an R source, and a Q source, removing the solvent after mixing for a preset time, and performing a first calcination treatment on the remaining solid to prepare the cathode material; or

[0019] Preparing a fast ion conductor from a lithium salt, a Ti source, an R source, and a Q source, and performing a first calcination treatment on the fast ion conductor and the core to prepare the cathode material;

[0020] The cathode material includes a core and a coating layer coated on at least a part of the surface of the core, the core contains lithium nickel manganese cobalt oxide; the coating layer contains a fast ion conductor, and the chemical formula of the fast ion conductor is Li 2- x R xTi3QO8, where 0 < x ≤ 0.1, the R element includes one or more elements of Na and K, and the Q element includes one or more elements of Co, Mg, Ni, and Mn.

[0021] In some embodiments, the lithium salt includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3, and may be one or more of LiOH and Li2CO3.

[0022] In some embodiments, the Ti source includes a Ti-containing compound containing a Ti-O bond; optionally, the Ti source includes one or more of titanium dioxide, tetrabutyl titanate, and titanyl sulfate.

[0023] In some embodiments, the R source includes one or more of a hydroxide, carbonate, sulfate, chloride, and nitrate containing the R element, and may be one or more of a hydroxide, carbonate, and nitrate containing the R element.

[0024] In some embodiments, the Q source includes one or more of a hydroxide, oxide, chloride, sulfate, and nitrate containing the Q element, and may be one or more of a hydroxide, oxide, and nitrate containing the Q element.

[0025] In some embodiments, the temperature of the first calcination treatment is 300°C - 700°C, and the time is 0 h - 24 h; optionally, the temperature of the first calcination treatment is 450°C - 550°C, and the time is 4 h - 6 h.

[0026] In some embodiments, the step of mixing the core with the mixed solution containing the lithium salt, Ti source, R source, and Q source includes: pouring solution B containing the lithium salt and R source into solution A containing the Ti source, Q source, and core.

[0027] In some embodiments, the chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements of Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B.

[0028] In some embodiments, the method for preparing the core includes: mixing a nickel cobalt lithium manganese oxide material precursor with a lithium source and then performing a second calcination treatment; or, mixing a nickel cobalt lithium manganese oxide material precursor with a lithium salt and an M source and then performing a second calcination treatment.

[0029] In some embodiments, the nickel cobalt manganese oxide lithium material precursor includes one or more of nickel cobalt manganese hydroxide, nickel cobalt manganese oxalate, and nickel cobalt manganese carbonate, and may be nickel cobalt manganese hydroxide.

[0030] In some embodiments, the molar ratio of the lithium element contained in the lithium source to the total elements contained in the lithium nickel cobalt manganese oxide material precursor is (1.02-1.05):1.

[0031] In some embodiments, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3, and may be one or more of LiOH and Li2CO3.

[0032] In some embodiments, the second calcination treatment includes a first stage and a second stage, the temperature of the first stage is 600°C-780°C, and the time is 2h-5h; the temperature of the second stage is 800°C-1000°C, and the time is 9h-12h.

[0033] The third aspect of the present application provides a positive electrode plate, comprising the fast ion conductor modified positive electrode material of the first aspect of the present application or the fast ion conductor modified positive electrode material prepared by the preparation method of the second aspect of the present application.

[0034] The fourth aspect of the present application provides a lithium-ion battery, comprising the positive electrode sheet of the third aspect of the present application.

[0035] The fifth aspect of the present application provides an electrical device, comprising the lithium-ion battery of the fourth aspect of the present application.

[0036] The fast ion conductor modified positive electrode material provided above has a coating layer containing a fast ion conductor. During the co-baking process of the coating raw material and the core, some cations of the fast ion conductor will penetrate into the core. Since the fast ion conductor is doped with R element, the R element enters the lithium site of the lithium nickel manganese cobalt oxide in the core to expand the interlayer spacing of the layered structure and increase the Li +Migration rate; The fast ion conductor coating has a stable lithium ion diffusion channel and constructs a complete coating on the surface of lithium nickel manganese cobalt oxide. Since the fast ion conductor containing the Ti element itself has good electronic conductivity, the coating improves the electronic conductivity of the positive electrode material. At the same time, the coating allows other ions including lithium ions to migrate therein, so the coating also improves the ion conductivity of the positive electrode material. In addition, the coating has a good effect of isolating the electrolyte, inhibiting the side reaction between the electrolyte and the surface of the core. Part of the Ti element diffuses into the interior of the lithium nickel manganese cobalt oxide to form a Ti-O bond. Since the Ti-O bond has a high bond energy, it can better inhibit the oxygen precipitation on the surface of the core. In summary, coating the core with a coating containing a fast ion conductor can improve the electronic conductivity and ionic conductivity of the positive electrode material, reduce the charge transfer impedance, increase the capacity of the positive electrode material and extend the life of the battery using the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0038] Figure 1 This is a scanning electron microscope image (SEM image) of the positive electrode material prepared in Example 2;

[0039] Figure 2 The distribution of Co element in the X-ray photoelectron spectrum of the positive electrode material prepared in Example 2;

[0040] Figure 3 The distribution of Ti element in the X-ray photoelectron spectrum of the positive electrode material prepared in Example 2. DETAILED DESCRIPTION

[0041] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.

[0042] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0043] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".

[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0045] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0046] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0047] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0048] In this application, unless otherwise specified, the size, particle size, and diameter generally refer to the average value. In this application, "particle size" and "particle size" have the same definition, both representing the average particle size of a sphere or a spheroid.

[0049] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.

[0050] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0051] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0052] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0053] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.

[0054] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0055] Lithium nickel manganese cobalt oxide (e.g., LiNi x Co y Mn 1−x−y O2, x ≥ 0.6) has become the most promising lithium battery positive electrode material due to its advantages such as high specific capacity and low cost. However, the primary particles of lithium nickel manganese cobalt oxide with medium nickel content are large, and its electronic conductivity and ionic conductivity are poor, which limits its capacity release.

[0056] The researchers of this application have found that coating the surface of lithium nickel manganese cobalt oxide with solid electrolyte or fast ion conductor material can significantly improve the ionic conductivity of the material surface. However, the electronic conductivity of common fast ion conductor materials is low, and they are generally used as solid electrolyte materials with strong dielectric properties.

[0057] Based on the above problems, the present invention covers the core surface with a titanium-containing fast ion conductor, and the fast ion conductor is doped with a lithium ion (Li + ) can enter the middle layer without destroying the core crystal structure, and the doping of lithium sites with elements of larger radius in fast ion conductors can expand the space of the core layered structure and improve Li+ Migration; fast ion conductors have a stable structure and maintain good permeability. They can build a complete coating on the surface of lithium nickel cobalt manganese oxide materials, effectively resisting HF corrosion, thereby improving cycle performance and reducing charge transfer impedance. Therefore, by coating with titanium-containing fast ion conductors, the lithium conductivity of the core material can be improved, its capacity can be increased, and the battery life can be extended.

[0058] One or more embodiments of the present application provide a fast ion conductor modified positive electrode material, comprising a core and a coating layer coated on at least a portion of the surface of the core; the core comprises lithium nickel manganese cobalt oxide, and the coating layer comprises a fast ion conductor, wherein the chemical formula of the fast ion conductor is Li 2-x R x Ti3QO8, 0<x≤1, R element includes one or more elements of Na and K, and Q element includes one or more elements of Co, Mg, Ni and Mn.

[0059] It should be noted that the "lithium nickel manganese cobalt oxide" in the context is not limited to LiNiMnCoO2. As long as it is an oxide containing lithium, nickel, manganese and cobalt elements, for example, oxides containing lithium, nickel, manganese and cobalt elements doped with other metal elements (such as transition metal elements) are within the scope of protection of this application.

[0060] The fast ion conductor modified positive electrode material contains a fast ion conductor in the coating layer. During the co-baking process of the coating raw material and the core, some cations of the fast ion conductor will penetrate into the core. Since the fast ion conductor is doped with R element, the R element enters the lithium site of the lithium nickel manganese cobalt oxide in the core to expand the interlayer spacing of the layered structure and increase the Li + Migration rate; The fast ion conductor coating has a stable lithium ion diffusion channel and constructs a complete coating on the surface of lithium nickel manganese cobalt oxide. Since the fast ion conductor containing the Ti element itself has good electronic conductivity, the coating improves the electronic conductivity of the positive electrode material. At the same time, the coating allows other ions including lithium ions to migrate therein, so the coating also improves the ion conductivity of the positive electrode material. In addition, the coating has a good effect of isolating the electrolyte, inhibiting the side reaction between the electrolyte and the surface of the core. Part of the Ti element diffuses into the interior of the lithium nickel manganese cobalt oxide to form a Ti-O bond. Since the Ti-O bond has a high bond energy, it can better inhibit the oxygen precipitation on the surface of the core. In summary, coating the core with a coating containing a fast ion conductor can improve the electronic conductivity and ionic conductivity of the positive electrode material, reduce the charge transfer impedance, increase the capacity of the positive electrode material and extend the life of the battery using the positive electrode material.

[0061] It can be understood that the technical solution of the present application does not exclude the situation where the core and / or the coating layer further include other materials, especially the situation where the core further includes other positive electrode active materials and / or the coating layer further includes other coating materials.

[0062] In some embodiments, the core mainly comprises or contains only lithium nickel manganese cobalt oxide, and the coating layer mainly comprises or contains only a chemical formula of Li 2-x R x Ti3QO8 represents a fast ion conductor.

[0063] In some embodiments, the fast ion conductor of the coating layer is directly coated on at least a portion of the surface of the lithium nickel manganese cobalt oxide of the core.

[0064] It is understood that the core and / or coating layer may further include other materials, but the content thereof should not be such that it becomes the main component, so as to avoid affecting the coating of the fast ion conductor on the lithium nickel manganese cobalt oxide.

[0065] As a non-limiting example, x may be 0.2, 0.5, 0.8 or 1, etc., without specific limitation.

[0066] In some embodiments, the sum of the mass proportions of the R element and Ti contained in the fast ion conductor in the positive electrode material is 0.1%-1%; for example, it can be but not limited to 0.1%, 0.12%, 0.14%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, 0.3%, 0.32%, 0.34%, 0.36%, 0.38%, 0.4%, 0.42%, 0.44%, 0.46%, 0.4 8%, 0.5%, 0.52%, 0.54%, 0.56%, 0.58%, 0.6%, 0.62%, 0.64%, 0.66%, 0.68%, 0.7%, 0.72%, 0.74%, 0.76%, 0.78%, 0.8%, 0.82%, 0.84%, 0.86%, 0.88%, 0.9%, 0.92%, 0.94%, 0.96%, 0.98%, 1% or the range between any two of the above mass percentages. When the sum of the mass percentages of the R element contained in the fast ion conductor and Ti in the positive electrode material is within the above range, it is beneficial to establish a complete coating on the surface of the lithium nickel manganese cobalt oxide while realizing ion micro-doping, thereby improving the electronic conductivity and ionic conductivity of the positive electrode material.

[0067] As a possible implementation, the mass ratio of Ti contained in the fast ion conductor in the cathode material is 1000 ppm - 3000 ppm; for example, it can be, but is not limited to, 1000 ppm, 1200 ppm, 1400 ppm, 1600 ppm, 1800 ppm, 2000 ppm, 2200 ppm, 2400 ppm, 2600 ppm, 2800 ppm, 3000 ppm or the range between any two of the above mass ratios, etc. When the mass ratio of Ti contained in the fast ion conductor in the cathode material is within the above range, it is beneficial to improve the electrochemical performance of the cathode material.

[0068] In some embodiments, the chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements among Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B.

[0069] It should be noted that the lithium nickel manganese cobalt oxide may also be doped with any possible impurity elements with a mass ratio less than 500 ppm in the inner core mixed in the production.

[0070] In some embodiments, the inner core includes one or more of single crystal particles, pseudo-single crystal particles, and polycrystalline particles. Thus, it is beneficial to combine with the titanium-containing fast ion conductor to improve the performance of the cathode material.

[0071] It should be noted that the "pseudo-single crystal particles" mentioned in the context refer to crystal particles formed by the aggregation of several or dozens of single crystal particles, and the number of their grain boundaries is much smaller than that of polycrystalline particles.

[0072] In some alternative embodiments, the volume average particle size Dv501 of the single crystal particles in the inner core is 2.5 μm - 4.5 μm; for example, it can be, but is not limited to, 2.5 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.5 μm or the range between any two of the above volume average particle sizes, etc.

[0073] As a possible embodiment, the volume average particle size Dv502 of the polycrystalline particles in the inner core is 1.5μm-18μm; for example, it can be but not limited to 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm or the range between any two of the above volume average particle sizes, etc.

[0074] Therefore, when the volume average particle size Dv50 of the single crystal particles and the polycrystalline particles in the inner core are respectively within the above ranges, it is beneficial to prepare a positive electrode material with excellent electrochemical properties.

[0075] It can be understood that when the inner core includes single crystal particles, quasi-single crystal particles and polycrystalline particles, the fast ion conductor modified positive electrode material obtained therefrom also includes single crystal particles, quasi-single crystal particles and polycrystalline particles. And the particle sizes of the single crystal particles, quasi-single crystal particles and polycrystalline particles in the finally obtained positive electrode material are similar to the particle sizes of the single crystal particles, quasi-single crystal particles and polycrystalline particles contained in the inner core.

[0076] In some exemplary embodiments, the fast ion conductor modified cathode material includes one or more of single crystal particles, quasi-single crystal particles, and polycrystalline particles.

[0077] In some optional embodiments, the volume average particle size Dv501 of single crystal particles in the fast ion conductor modified positive electrode material is 2.5μm-4.5μm; for example, it can be but not limited to 2.5μm, 2.6μm, 2.8μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.5μm or the range between any two of the above volume average particle sizes, etc.

[0078] As a possible embodiment, the volume average particle size Dv502 of the polycrystalline particles in the fast ion conductor modified positive electrode material is 1.5μm-18μm; for example, it can be but not limited to 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm, 15μm or the range between any two of the above volume average particle sizes, etc.

[0079] It should be noted that the volume average particle size Dv50 mentioned above refers to the particle size corresponding to when the cumulative volume particle size distribution percentage of the sample reaches 50%. The particle size distribution can be determined by a particle size distribution instrument.

[0080] One or more embodiments of the present application provide a method for preparing a fast ion conductor modified positive electrode material, which can be used to prepare the above-mentioned fast ion conductor modified positive electrode material; the preparation method comprises the following steps:

[0081] A mixture comprising a core, a lithium salt, a Ti source, an R source and a Q source is subjected to a first calcination treatment to prepare a positive electrode material; or, the core is immersed in a mixed solution comprising a lithium salt, a Ti source, an R source and a Q source, filtered and separated after immersion for a preset time, and the solid obtained by filtration and separation is subjected to a first calcination treatment to prepare a positive electrode material; or, the core is mixed with a mixed solution comprising a lithium salt, a Ti source, an R source and a Q source, the solvent is removed after mixing for a preset time, and the remaining solid is subjected to a first calcination treatment to prepare a positive electrode material; or, a fast ion conductor is prepared from a lithium salt, a Ti source, an R source and a Q source, and the fast ion conductor and the core are subjected to a first calcination treatment to prepare the positive electrode material;

[0082] The positive electrode material includes a core and a coating layer coated on at least a portion of the surface of the core, wherein the core includes lithium nickel manganese cobalt oxide; the coating layer includes a fast ion conductor, and the chemical formula of the fast ion conductor is Li 2-x R x Ti3QO8, 0<x≤0.1, R element includes one or more elements of Na and K, and Q element includes one or more elements of Co, Mg, Ni and Mn.

[0083] In the prepared coated modified positive electrode material, the composition, structure and properties of the lithium nickel manganese cobalt oxide in the core and the fast ion conductor in the coating layer are as described above and will not be repeated in the method.

[0084] It should be noted that the "first roasting treatment", "second roasting treatment", "first stage" and "second stage" mentioned in the context are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second" and the like only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0085] Understandably, the method for preparing the fast ion conductor modified positive electrode material provided in the present application uses a fast ion conductor that takes into account both electronic conductivity and ionic conductivity to coat lithium nickel manganese cobalt oxide, and at the same time utilizes the stable coating layer and the surface doping effect formed during the roasting process to further enhance the ionic conductivity and stability of lithium nickel manganese cobalt oxide. Therefore, by coating lithium nickel manganese cobalt oxide with a titanium-containing fast ion conductor, the electronic conductivity and ionic conductivity of the positive electrode material are improved, the material capacity is improved, and the structural stability of the material is improved. At the same time, the preparation method is simple in process, low in cost, and easy to scale up for production.

[0086] It can be understood that removing the solvent by filtering and separating is beneficial to removing impurities in the mixed solution together with the solvent, thereby improving the purity of the prepared positive electrode material.

[0087] In some exemplary embodiments, the preset time is 0.5h-2h; for example, it may be but is not limited to 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h or a range between any two of the above times, etc.

[0088] In some optional embodiments, the solvent is removed by drying and volatilization, which makes it difficult to remove impurities in the mixed solution, which may affect the purity of the prepared positive electrode material.

[0089] In some embodiments, the lithium salt includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.

[0090] In an alternative embodiment, the lithium salt includes one or more of LiOH and Li2CO3.

[0091] As a possible implementation, the Ti source includes a Ti-containing compound containing a Ti—O bond.

[0092] In some embodiments, the Ti source includes one or more of titanium dioxide, tetrabutyl titanate, and titanyl sulfate.

[0093] As a possible implementation, the R source includes one or more of hydroxides, carbonates, sulfates, chlorides and nitrates containing the R element.

[0094] In some exemplary embodiments, the R source includes one or more of a hydroxide, a carbonate, and a nitrate containing an R element.

[0095] In some embodiments, the Q source includes one or more of hydroxides, oxides, chlorides, sulfates, and nitrates containing a Q element.

[0096] As a possible implementation, the Q source includes one or more of hydroxides, oxides, and nitrates containing Q elements.

[0097] In some embodiments, the temperature of the first calcination treatment is 300°C - 700°C; for example, it can be, but is not limited to, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, or the range between any two of the above temperatures, etc.

[0098] In some alternative embodiments, the temperature of the first calcination treatment is 450°C - 550°C.

[0099] As a possible implementation, the time of the first calcination treatment is 0h - 24h; for example, it can be, but is not limited to, 0h, 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h, or the range between any two of the above times, etc.

[0100] In some of these embodiments, the time of the first calcination treatment is 4h - 6h.

[0101] It should be noted that the temperature and time of the first calcination treatment can be combined in any suitable manner, and both can be selected from any of the temperatures and times of the first calcination treatment described herein respectively.

[0102] When the temperature and time of the first calcination treatment are respectively within the above ranges, it is beneficial to obtain a cathode material with appropriate size, morphology, and specific microstructure.

[0103] In some embodiments, the step of mixing the core with the mixed solution containing a lithium salt, a Ti source, an R source, and a Q source includes: pouring solution B containing the lithium salt and the R source into solution A containing the Ti source, the Q source, and the core.

[0104] In some embodiments, the chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements selected from Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B.

[0105] As a possible implementation, the method for preparing the inner core includes: mixing a nickel cobalt manganese oxide lithium material precursor with a lithium source and then performing a second calcination treatment; or, mixing a nickel cobalt manganese oxide lithium material precursor with a lithium salt and an M source and then performing a second calcination treatment.

[0106] In some optional embodiments, the nickel cobalt manganese oxide lithium material precursor includes one or more of nickel cobalt manganese hydroxide, nickel cobalt manganese oxalate, and nickel cobalt manganese carbonate, and may be nickel cobalt manganese hydroxide.

[0107] In some exemplary embodiments, the molar ratio of the lithium element contained in the lithium source to the total elements contained in the nickel cobalt manganese oxide material precursor is (1.02-1.05):1; for example, it can be but not limited to 1.02:1, 1.025:1, 1.03:1, 1.035:1, 1.04:1, 1.045:1, 1.05:1 or a range between any two of the above molar ratios, etc.

[0108] In some optional embodiments, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3, and may be one or more of LiOH and Li2CO3.

[0109] In some embodiments, the second calcination process includes a first stage and a second stage.

[0110] As a possible implementation manner, the temperature of the first stage is 600°C-780°C; for example, it can be but not limited to 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 740°C, 760°C, 780°C or a range between any two of the above temperatures.

[0111] In some optional embodiments, the duration of the first stage is 2 hours to 5 hours; for example, it may be but is not limited to 2 hours, 3 hours, 4 hours, 5 hours or a range between any two of the above times.

[0112] It should be noted that the temperature and time of the first stage can be combined in any appropriate manner, and both can be selected from any temperature and time of the first stage described in this document.

[0113] As a possible implementation manner, the temperature of the second stage is 800°C-1000°C; for example, it can be but not limited to 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C or a range between any two of the above temperatures.

[0114] In some optional embodiments, the time of the second stage is 9h-12h; for example, it can be but not limited to 9h, 10h, 11h, 12h or a range between any two of the above times, etc. It should be noted that the temperature and time of the second stage can be combined in any appropriate manner, and both can be selected from any temperature and time of the second stage described in this article.

[0115] One or more embodiments of the present application provide a positive electrode plate, including a fast ion conductor modified positive electrode material provided in the present application or a fast ion conductor modified positive electrode material prepared by the preparation method provided in the present application.

[0116] One or more embodiments of the present application provide a lithium-ion battery, comprising the above-mentioned positive electrode plate.

[0117] The lithium-ion battery of the present application comprises the above-mentioned fast ion conductor modified positive electrode material, has higher capacity and first efficiency, lower pulse resistance and excellent cycle performance.

[0118] One or more embodiments of the present application provide an electrical device, including the above-mentioned lithium-ion battery. The electrical device can be an electric car, an electric bicycle, an electric two-wheeled vehicle, an electric car power system, an energy storage system or a mobile storage device, etc., without limitation.

[0119] The electric device of the present application includes the lithium-ion battery provided by the present application, and thus has at least the same advantages as the lithium-ion battery.

[0120] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.

[0121] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0122] 1. Preparation of positive electrode materials

[0123] Example 1

[0124] Step S1: Ni 0.6 Co 0.1 Mn 0.3(OH)2 (precursor, Dv50 = 3.2 μm), Li2CO3 (lithium source) are mixed according to the molar ratio of Ni, Co, Mn total metals contained in the precursor and lithium element contained in the lithium source of 1:1.05, SrCO3 and Nb2O5 are added, and the mixture is placed in a high-speed mixer for mixing. The speed of the high-speed mixer is 950 rpm / min, and the mixing time is 50 min. After fully mixing, a mixture is obtained. Among them, based on the mass of the final core, the amount of Sr added is 1000 ppm, and the amount of Nb added is 700 ppm. The mixture is placed in an oxygen atmosphere and roasted at 600 ° C for 3 hours, and then the temperature is increased to 950 ° C and roasted for 10 hours to obtain a roasted product. The roasted product is crushed, sieved, washed with water, and dried to obtain a core. The chemical formula of the core is LiNi 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 O2, Dv50 is 3.5μm.

[0125] Step S2, tetrabutyl titanate and cobalt nitrate are dispersed in 500 mL of ethanol solution, and then lithium hydroxide and sodium hydroxide are added (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05), and the reaction is carried out for 2 hours. Then, the mixture is filtered and washed, vacuum dried at 100°C for 3 hours, and then placed in an air atmosphere at 870°C for 6 hours, and then ground and sieved to obtain the fast ion conductor LiNaTi3CoO8.

[0126] Step S3, add LiNaTi3CoO8 powder to the core material, mix well, and then place in air atmosphere at 500°C for 6h to form LiNi 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material, wherein the mass proportion of Ti in the positive electrode material is 1000ppm, the mass proportion of Na in the positive electrode material is 150ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.115%.

[0127] Example 2

[0128] The difference between Example 2 and Example 1 is that in step S3 of Example 2, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material, the mass proportion of Na in the positive electrode material, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; Example 2 is specifically as follows:

[0129] Step S1 and step S2 are the same as step S1 and step S2 in embodiment 1.

[0130] Step S3, add LiNaTi3CoO8 powder to the core material, mix well, and then place in air atmosphere at 500°C for 6h to form LiNi 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 2000ppm, the mass proportion of Na in the positive electrode material is 300ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.23%.

[0131] Example 3

[0132] The difference between Example 3 and Example 1 is that in step S3 of Example 3, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material, the mass proportion of Na in the positive electrode material, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; Example 2 is specifically as follows:

[0133] Step S1 and step S2 are the same as step S1 and step S2 in embodiment 1.

[0134] Step S3, add LiNaTi3CoO8 powder to the core material, mix well, and then place in air atmosphere at 500°C for 6h to form LiNi 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 500ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.35%.

[0135] Example 4

[0136] Step S1 is the same as step S1 in Example 1.

[0137] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 1000ppm, the mass proportion of Na in the positive electrode material is 600ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.16%.

[0138] Example 5

[0139] The difference between Example 5 and Example 4 is that in step S2 of Example 5, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material, the mass proportion of Na in the positive electrode material, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; Example 5 is specifically as follows:

[0140] Step S1 is the same as step S1 in Example 1.

[0141] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 2000ppm, the mass proportion of Na in the positive electrode material is 800ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.28%.

[0142] Example 6

[0143] The difference between Example 6 and Example 4 is that in step S2 of Example 6, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; the details of Example 6 are as follows:

[0144] Step S1 is the same as step S1 in Example 1.

[0145] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 500ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.35%.

[0146] Example 7

[0147] The difference between Example 7 and Example 4 is that in step S2 of Example 7, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; the details of Example 7 are as follows:

[0148] Step S1 is the same as step S1 in Example 1.

[0149] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 4000ppm, the mass proportion of Na in the positive electrode material is 600ppm, and the mass proportion of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 4.6%.

[0150] Example 8

[0151] The difference between Example 8 and Example 4 is that in step S2 of Example 8, the mass proportion of Ti contained in the fast ion conductor in the positive electrode material and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material are different; the details of Example 8 are as follows:

[0152] Step S1 is the same as step S1 in Example 1.

[0153] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007A coating layer containing a fast ion conductor LiNaTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 500ppm, the mass proportion of Na in the positive electrode material is 80ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.058%.

[0154] Example 9

[0155] The difference between Example 9 and Example 6 is that the Q source used in Example 9 is different; the details of Example 9 are as follows:

[0156] Step S1 is the same as step S1 in Example 1.

[0157] Step S2, disperse tetrabutyl titanate and magnesium oxide in 500mL ethanol solution. Then add 200g of the core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Mg contained in magnesium oxide: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and then place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiNaTi3MgO8 is coated on at least part of the surface of O2 to obtain a positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 500ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.35%.

[0158] Example 10

[0159] The difference between Example 10 and Example 6 is that the R source used in Example 10 is different; the details of Example 10 are as follows:

[0160] Step S1 is the same as step S1 in Example 1.

[0161] Step S2, disperse tetrabutyl titanate and magnesium oxide in 500mL ethanol solution. Then add 200g of the core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and potassium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Mg contained in magnesium oxide: K contained in potassium hydroxide: Li contained in lithium hydroxide is 3:1:0.5:0.1) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 At least part of the surface of O2 is coated with a fast ion conductor Li 1.5 K 0.5 The coating layer of Ti3MgO8 is used to prepare the positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of K in the positive electrode material is 400ppm, and the mass proportion of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.34%.

[0162] Embodiment 11

[0163] The difference between Example 11 and Example 6 is that the Q source used in Example 11 is different; the details of Example 11 are as follows:

[0164] Step S1 is the same as step S1 in Example 1.

[0165] Step S2, disperse tetrabutyl titanate and nickel acetate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Ni contained in nickel acetate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:0.2:0.85) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 At least part of the surface of O2 is coated with a fast ion conductor Li 1.8 Na 0.2The coating layer of Ti3NiO8 is used to prepare the positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 500ppm, and the mass proportion of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.35%. Example 12

[0166] The difference between Example 12 and Example 6 is that the Q source used in Example 12 is different; the details of Example 12 are as follows:

[0167] Step S1 is the same as step S1 in Example 1.

[0168] Step S2, disperse tetrabutyl titanate and manganese nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and sodium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Mn contained in manganese nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 3:1:0.8:0.25) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 At least part of the surface of O2 is coated with a fast ion conductor Li 1.2 Na 0.8 The coating layer of Ti3MnO8 was used to prepare the positive electrode material. Among them, the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 500ppm, and the mass proportion of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.35%.

[0169] In Comparative Example 1, no coating was performed.

[0170] Step S1 is the same as step S1 in Example 1.

[0171] Step S2, calcining the inner core at 500° C. for 6 hours in an air atmosphere to obtain a positive electrode material.

[0172] Comparative Example 2

[0173] Step S1 is the same as step S1 in Example 1.

[0174] Step S2, tetrabutyl titanate and cobalt nitrate are dispersed in 500 mL of ethanol solution, and then lithium hydroxide is added (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Li contained in lithium hydroxide is 3:1:0.05), and the reaction is carried out for 2 hours. Then, the mixture is filtered and washed, vacuum dried at 100°C for 3 hours, and then placed in an air atmosphere at 870°C for 6 hours, and then ground and sieved to obtain the fast ion conductor LiTi3CoO8.

[0175] Step S3, add LiTi3CoO8 powder to the core material, mix well, and then place in air atmosphere at 500°C for 6h to form LiNi 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material, wherein the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 0ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.3%.

[0176] Comparative Example 3

[0177] Step S1 is the same as step S1 in Example 1.

[0178] Step S2, disperse tetrabutyl titanate and cobalt nitrate in 500mL ethanol solution. Then add 200g of the core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide (the molar ratio of Ti contained in tetrabutyl titanate: Co contained in cobalt nitrate: Li contained in lithium hydroxide is 3:1:0.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150℃ for 1 h, and place at 500℃ in air atmosphere for 6 hours to form LiNi in the core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor LiTi3CoO8 is coated on at least part of the surface of O2 to obtain a positive electrode material, wherein the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Na in the positive electrode material is 0ppm, and the sum of the mass proportions of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.3%.

[0179] Comparative Example 4

[0180] Step S1 is the same as step S1 in Example 1.

[0181] Step S2 and cobalt nitrate are dispersed in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, which is recorded as solution A. Lithium hydroxide and sodium hydroxide (the molar ratio of Co contained in cobalt nitrate: Na contained in sodium hydroxide: Li contained in lithium hydroxide is 1:1:0.05) are fully dissolved in 10g of deionized water, which is recorded as solution B. Under vigorous stirring, solution B is slowly poured into solution A and reacted for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place it at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer of a fast ion conductor LiNaCoO4 is coated on at least a portion of the surface of O2 to obtain a positive electrode material, wherein the mass proportion of Na in the positive electrode material is 500 ppm.

[0182] Comparative Example 5

[0183] Step S1 is the same as step S1 in Example 1.

[0184] Step S2, disperse tetrabutyl titanate and lanthanum nitrate in 500mL ethanol solution. Then add 200g of the inner core and stir slowly, recorded as solution A. Fully dissolve lithium hydroxide and aluminum nitrate (the molar ratio of Ti contained in tetrabutyl titanate: La contained in lanthanum nitrate: Al contained in aluminum nitrate: Li contained in lithium hydroxide is 1:1:1:1.05) in 10g of deionized water, recorded as solution B. Under vigorous stirring, slowly pour solution B into solution A and react for 0.5 h. Then filter and wash, vacuum dry at 150°C for 1 h, and place at 500°C in an air atmosphere and calcine for 6 hours to form LiNi in the inner core. 0.6 Co 0.0993 Mn 0.299 Sr 0.001 Nb 0.0007 A coating layer containing a fast ion conductor Li2AlTiLaO6 is coated on at least part of the surface of O2 to obtain a positive electrode material, wherein the mass proportion of Ti in the positive electrode material is 3000ppm, the mass proportion of Al in the positive electrode material is 1500ppm, and the mass proportion of Na, K and Ti contained in the fast ion conductor in the positive electrode material is 0.45%.

[0185] The positive electrode material prepared in Example 2 was scanned using a scanning electron microscope, and the results were as follows: Figure 1 As shown. At the same time, X-ray photoelectron spectroscopy analysis was performed, and the distribution of Co elements in the spectrum was as follows Figure 2 As shown, the distribution of Ti element in the energy spectrum is as follows Figure 3 As shown. Figure 1-3It can be seen that the elements on the surface of the positive electrode material are evenly distributed, indicating that the coating is uniform; the titanium-containing fast ion conductor with a stable structure can improve the electronic conductivity of the positive electrode material.

[0186] 2. Electrochemical performance test

[0187] The positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride prepared in the above embodiments and comparative examples were mixed in a mass ratio of 95:2.5:2.5, and an appropriate amount of N-methylpyrrolidone was added as a dispersant, and ground into a slurry; then the slurry was evenly coated on an aluminum foil, vacuum dried at 120°C for 10 hours, and the dried electrode was rolled with a roller machine, and the aluminum foil was cut with a slicer to cut into a circular electrode with a diameter of 1.2 cm, and the loading amount of the active material was controlled at 12 mg / cm 2 about.

[0188] The liquid battery was assembled in an argon atmosphere glove box, in which a lithium sheet with a diameter of 1.5 cm was used as the negative electrode, a 12 μm PP / PE film was used as the separator, and 10 μL of 1 mol / L LiPF6 carbonate polyelectrolyte was added at the interface between the positive electrode sheet, the lithium negative electrode and the electrolyte. The CR2032 button battery was assembled in an environment with a water partial pressure ≤0.1 ppm and an oxygen partial pressure ≤0.1 ppm.

[0189] The assembled button lithium-ion battery was subjected to capacity test and cycle performance test under the test conditions of LR 2032.

[0190] The cycle performance test method is: at 45℃, charge and discharge the button cell at 1C for 50 cycles, with a voltage range of 3.0V-4.5V, vs. Li + / Li.

[0191] The capacity test method is: at 25℃, charge and discharge the button cell at 0.1C for 1 week, with a voltage range of 2.8V-4.4V, vs. Li + / Li.

[0192] The test results of the first-cycle discharge specific capacity, first-cycle coulomb efficiency, DC pulse impedance when fully charged, and fifty-cycle high-temperature cycle capacity retention rate of the above-mentioned embodiments and comparative examples are shown in Table 2.

[0193] Table 2

[0194]

[0195] By comparing the results of Examples 1-12 and Comparative Examples 1-5, it can be seen that compared with Comparative Examples 1-5, Examples 1-12 have higher discharge specific capacity, first efficiency and cycle capacity retention rate, and lower DC pulse resistance; indicating that the fast ion conductor Li 2-x R x Ti3QO8 (0<x≤1, R element includes one or more elements of Na and K, Q element includes one or more elements of Co, Mg, Ni and Mn) coated with lithium nickel manganese cobalt oxide can improve the capacity, first efficiency and cycle capacity retention rate of the positive electrode material, and at the same time reduce the DC pulse resistance. This is because: the fast ion conductor Li 2-x R x R-doping of lithium sites in Ti3QO8 can expand the interlayer spacing of the layered structure and increase the Li + Migration; The fast ion conductor coating has a stable lithium ion diffusion channel and constructs a complete coating on the surface of lithium nickel manganese cobalt oxide. Since the fast ion conductor containing the Ti element itself has good electronic conductivity, the coating improves the electronic conductivity of the positive electrode material. At the same time, the coating allows other ions including lithium ions to migrate therein, so the coating also improves the ion conductivity of the positive electrode material. Titanium-containing fast ion conductor coating can improve the conductivity of lithium nickel manganese cobalt oxide, reduce charge transfer impedance, increase its capacity and extend battery life.

[0196] From the comparison of the results of Example 2 and Comparative Example 1, it can be seen that although the synthesis conditions are the same, after the surface of the positive electrode material is coated with the fast ion conductor in Example 2, the battery impedance is reduced, and the discharge capacity, coulomb efficiency and capacity retention rate are greatly improved. The titanium-containing fast ion conductor improves the ionic conductivity and electronic conductivity of lithium nickel manganese cobalt oxide, resulting in a decrease in impedance and an increase in discharge capacity. The coating layer effectively resists HF corrosion and improves the battery cycle stability.

[0197] By comparing the results of Example 3 with Comparative Example 2, and Example 6 with Comparative Example 3, it can be seen that under the same synthesis conditions and the amount of Ti element added, the fast ion conductors of Example 3 and Example 6 are doped with R ions, and their capacity, impedance and cycle performance are optimized compared with Comparative Example 2 and Comparative Example 3. The data show that the coating of titanium-containing fast ion conductors has better capacity improvement and impedance reduction effects.

[0198] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0199] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A fast ion conductor modified positive electrode material, characterized in that: include: a core comprising lithium nickel manganese cobalt oxide; and A coating layer is coated on at least a portion of the surface of the core, wherein the coating layer comprises a fast ion conductor, wherein the chemical formula of the fast ion conductor is Li 2-x R x Ti3QO8, 0<x≤1, R element includes one or more elements of Na and K, and Q element includes one or more elements of Co, Mg, Ni and Mn.

2. The fast ion conductor modified positive electrode material according to claim 1, characterized in that: The sum of the mass proportions of the R element contained in the fast ion conductor and Ti in the positive electrode material is 0.1%-1%; and / or The mass proportion of Ti contained in the fast ion conductor in the positive electrode material is 1000ppm-3000ppm.

3. The fast ion conductor modified positive electrode material according to claim 1, characterized in that: The positive electrode material has at least one of the following characteristics (1)-(3): (1) The fast ion conductor is coated on at least a portion of the surface of the lithium nickel manganese cobalt oxide; (2) The chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements selected from Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B; (3) The inner core includes one or more of single crystal particles, quasi-single crystal particles and polycrystalline particles; Optionally, the volume average particle size Dv501 of the single crystal particles is 2.5 μm-4.5 μm; Optionally, the volume average particle size Dv502 of the polycrystalline particles is 1.5 μm-18 μm.

4. A method for preparing a fast ion conductor modified positive electrode material, characterized in that: The steps include: The positive electrode material is prepared by subjecting a mixture comprising a core, a lithium salt, a Ti source, an R source and a Q source to a first calcination treatment; or The core is immersed in a mixed solution containing a lithium salt, a Ti source, an R source and a Q source, and filtered and separated after immersion for a preset time, and the solid obtained by filtration and separation is subjected to a first calcination treatment to prepare the positive electrode material; or The core is mixed with a mixed solution containing a lithium salt, a Ti source, an R source and a Q source, the solvent is removed after mixing for a preset time, and the remaining solid is subjected to a first calcination treatment to prepare the positive electrode material; or A fast ion conductor is prepared from a lithium salt, a Ti source, an R source and a Q source, and the fast ion conductor and the core are subjected to a first calcination treatment to prepare the positive electrode material; The positive electrode material comprises a core and a coating layer coated on at least a portion of the surface of the core, wherein the core comprises lithium nickel manganese cobalt oxide; the coating layer comprises a fast ion conductor, and the chemical formula of the fast ion conductor is Li 2-x R x Ti3QO8, 0<x≤0.1, R element includes one or more elements of Na and K, and Q element includes one or more elements of Co, Mg, Ni and Mn.

5. The preparation method according to claim 4, characterized in that: The preparation method comprises at least one of the following conditions (1)-(3): (1) The lithium salt includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3, and can be one or more of LiOH and Li2CO3; (2) The Ti source includes a Ti-containing compound containing a Ti-O bond; optionally, the Ti source includes one or more of titanium dioxide, tetrabutyl titanate and titanyl sulfate; (3) The R source includes one or more of hydroxides, carbonates, sulfates, chlorides and nitrates containing the R element, and can be selected from one or more of hydroxides, carbonates and nitrates containing the R element; (4) The Q source includes one or more of the hydroxide, oxide, chloride, sulfate and nitrate containing the Q element, and can be selected from one or more of the hydroxide, oxide and nitrate containing the Q element; (5) The temperature of the first calcination treatment is 300° C.-700° C., and the time is 0 h-24 h; optionally, the temperature of the first calcination treatment is 450° C.-550° C., and the time is 4 h-6 h; (6) The step of mixing the core with a mixed solution containing a lithium salt, a Ti source, an R source and a Q source comprises: pouring a solution B containing a lithium salt and an R source into a solution A containing a Ti source, a Q source and the core.

6. The preparation method according to any one of claims 4 to 5, characterized in that: The chemical formula of the lithium nickel manganese cobalt oxide is LiNi a Co b Mn c M 1-a-b-c O 2+d , where 0.5 ≤ a ≤ 0.98, 0.01 < b < 0.3, 0.01 < c < 0.5, 0 ≤ 1 - a - b - c ≤ 0.05, -0.05 ≤ d ≤ 0.05, and the M element includes one or more elements selected from Mg, Al, Ti, Zr, W, Y, Nb, Mo, Sr, Si, F, La, Sb, Ta, Sn, Bi, and B.

7. The preparation method according to claim 6, characterized in that: The preparation method of the inner core comprises: The nickel cobalt lithium manganese oxide material precursor is mixed with a lithium source and then subjected to a second calcination treatment; or, the nickel cobalt lithium manganese oxide material precursor is mixed with a lithium salt and an M source and then subjected to a second calcination treatment; Optionally, the nickel cobalt manganese oxide lithium material precursor includes one or more of nickel cobalt manganese hydroxide, nickel cobalt manganese oxalate, and nickel cobalt manganese carbonate, and may be nickel cobalt manganese hydroxide; Optionally, the molar ratio of the lithium element contained in the lithium source to the total elements contained in the lithium nickel cobalt manganese oxide material precursor is (1.02-1.05):1; Optionally, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3, and may be one or more of LiOH and Li2CO3; Optionally, the second calcination treatment includes a first stage and a second stage, the temperature of the first stage is 600°C-780°C, and the time is 2h-5h; the temperature of the second stage is 800°C-1000°C, and the time is 9h-12h.

8. A positive electrode sheet, characterized in that: A fast ion conductor modified positive electrode material comprising the fast ion conductor modified positive electrode material as claimed in any one of claims 1 to 3 or a fast ion conductor modified positive electrode material prepared by the preparation method as claimed in any one of claims 4 to 7.

9. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 8.

10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.